2019
DOI: 10.1016/j.foostr.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Physical and interfacial characterization of phytosterols in oil-in-water triacylglycerol-based emulsions

Abstract: of the phytosterol within the carrier matrix. Currently, there is a limited amount of knowledge on how phytosterols interact at oil-water interfaces, despite research indicating that these interfaces could promote the crystallization of phytosterols and thus decrease bioaccessibility.In order to fill this knowledge gap, this work expands upon a previously studied emulsion system for encapsulating phytosterols and addresses whether phytosterols can crystalize at an oil-in-water emulsion interface. Images from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 49 publications
0
17
0
1
Order By: Relevance
“…A similar decrease in the droplet size of WPI stabilised emulsions with phytosterol addition has been documented in previous work and is believed to be due to a synergistic interaction between phytosterols and whey protein at the oil-in-water interface. Phytosterol and whey protein can decrease interfacial tension at the oil/water interface of the system to a greater extent together, than each compound can achieve separately (Zychowski, Mettu, Dagastine, O'Mahony, & Auty, 2017). While all 1.0 µm emulsion droplets required 1 pass at 300 bar to form a stable, monomodal emulsion distribution, the phytosterol emulsion formulations with an average of 0.2 µm sized droplets required homogenisation at 1000 bar and either 4, 3, or 5 passes for the WPI, WPI + lecithin, and WPI + MAG samples, respectively.…”
Section: The Effect Of Lecithin and Mag On Phytosterol Crystallisatiomentioning
confidence: 99%
“…A similar decrease in the droplet size of WPI stabilised emulsions with phytosterol addition has been documented in previous work and is believed to be due to a synergistic interaction between phytosterols and whey protein at the oil-in-water interface. Phytosterol and whey protein can decrease interfacial tension at the oil/water interface of the system to a greater extent together, than each compound can achieve separately (Zychowski, Mettu, Dagastine, O'Mahony, & Auty, 2017). While all 1.0 µm emulsion droplets required 1 pass at 300 bar to form a stable, monomodal emulsion distribution, the phytosterol emulsion formulations with an average of 0.2 µm sized droplets required homogenisation at 1000 bar and either 4, 3, or 5 passes for the WPI, WPI + lecithin, and WPI + MAG samples, respectively.…”
Section: The Effect Of Lecithin and Mag On Phytosterol Crystallisatiomentioning
confidence: 99%
“…Phytosterols were multifunctional bioactive substances widely present in plants. , Studies have revealed that campesterol, stigmasterol, and sitosterol are the main biosynthetic end products of phytosterol, and they could significantly lower cholesterol and plasma triglycerides. , As shown in Table , the variation trend of the three sterols in the germination process was consistent. The phytosterol contents increased and peaked at 18 h, with the campesterol, stigmasterol, and sitosterol contents of 12.66, 16.72, and 9.73% higher than their initial contents, respectively.…”
Section: Resultsmentioning
confidence: 82%
“…14 Phytosterols were multifunctional bioactive substances widely present in plants. 23,24 Studies have revealed that campesterol, stigmasterol, and sitosterol are the main biosynthetic end products of phytosterol, and they could significantly lower cholesterol and plasma triglycerides. 25,26 As shown in Table 1, the variation trend of the three sterols in the germination process was consistent.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The particle size was influenced according to the interfacial tension of the emulsion. Thus, it was known that whey protein will move to the interface and will influence the interfacial tension on an oil/water surface, separately or synergistically and this is possible because of the amphiphilic characteristic present in whey protein (ZYCHOWSKI et al, 2018). According to McClementes (2002), "Food emulsion droplets usually have an average diameter in the range of 0.1 to 100 μm".…”
Section: Particle Sizementioning
confidence: 99%
“…Thus, it was verified the formation of micro-droplets in both emulsions, however in the emulsion processed by Turrax it was possible to verify that there was a reduction in the size of these droplets according to Figure 3, confirming the particle size results. The size of the droplet can be observed through the home microscopy of the fat present in the emulsion that forms a crystal lattice in optical response to polarization due to light birefringence and is widely used in food matrices (ZYCHOWSKI et al, 2018).…”
Section: Microscopymentioning
confidence: 99%